A causal association between esophageal cancer and the oral microbiome: a Mendelian randomization study based on an Asian population - Hu, Keke; Huang, Ting; Zhang, Yiming; Ye, Zhifeng; Guo, Junhua (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundPrevious studies have suggested a crosstalk between the oral microbiome and esophageal cancer (EC), but the exact relationship is unclear. This study aimed to investigate the causal relationship between changes in the oral microbiome and EC by Mendelian randomization (MR).Materials and methodsIn the study, bidirectional MR analyses were conducted using genome-wide association study data from the oral microbiomes from the 4D-SZ cohort and EC data from the BioBank Japan cohort. Multiple sensitivity tests, including Cochrane’s Q statistic, MR-Egger intercept, and MR-PRESSO, were used to assess and validate the relative stability of the resulting data at various levels.ResultsAmong the 3,117 samples studied, 73 oral microbiomes were found to be statistically causally associated with EC, 38 of which were considered protective factors. According to species analyses, positive results were concentrated in three phyla: Firmicutes (29 species), Patescibacteria (18 species), and Actinobacteria (9 species). It was also determined that Parvimonas micra, Aggregatibacter, and Clostridia had a negative causal relationship, implying that EC caused a decrease in the counts. Following p-value correction, periodonticum_C, unclassified_mgs_3234, and unclassified_mgs_45 were identified as having a strong evidence-grade causal relationship with EC. There was no strong evidence in the results of the inverse MR analyses of EC to the oral microbiome. The sensitivity analysis confirmed the robustness of the findings.ConclusionThis study discovered a bidirectional causal relationship between the oral microbiome and EC, which may provide new insights into the future use of the microbiome for early screening and probiotic therapy.